Penelitian Kemasan Kripik Singkong - Susmirah Suryandari (Balai Besar Kimia dan Kemasan, 1998)
The plastik material have been used on the research of casava chip packaging. Three kinds of plastic packaging material were used, i.e. polypropylene, polyethylene and polystyrene. The key parameter evaluated are global migration (by using aquadest, acetic acid 4 %, ethanol 20 % and n-heptana) and equilibrarium moisture content at the difference humidity, time andthickness. The migration process is influenced by temperature, contact time, aqueous stimulant and the kind of plastic material. The result shows that 0, 08 mm polypropylene plastic bag is more suitable for casava chip packaging than the other materials. In this case, two conditioan of the global migration of polypropylene plastic are 0,9625 mg/dm' (at. 95 °C, 2 hours, 50 mlaquadest) and 0,425 mg/dm' (at 40 °C, 30 minutes, 50 ml aquadest).